KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS BLOOD DONATION AMONG UNIMAS UNDERGRADUATE NURSING STUDENTS - HELEN, SEMPON (Universiti Malaysia Sarawak (UNIMAS), 2024)
Background: The Ministry of Health Malaysia's Blood Donation dashboard ranks Sarawak seventh among Malaysian states for blood donations (MOH, 2024). Barriers to donation include lack of awareness, fear, and medical conditions. Ensuring a safe and sufficient blood supply is crucial for national healthcare policies (WHO, 2023). Raising awareness among society and nursing students is essential to maintain a reliable blood supply. Objectives: To assess the level of knowledge, attitude, and practice habit towards blood donation among UNIMAS undergraduate nursing students. Methodology: A descriptive cross-sectional quantitative study was conducted with 165 randomly selected undergraduate nursing students from FMHS, UNIMAS. Data was collected using a questionnaire with four sections: socio-demographics, knowledge, attitude, and practice. The data was analyzed using IBM SPSS Statistics 27.0. Results: The study found that 93.3% of nursing students had adequate knowledge, while 6.7% had inadequate knowledge of blood donation. Positive attitudes were observed in 92.7% of students, with 7.3% displaying negative attitudes. Despite this, only 19.4% had donated blood, while 80.6% had not. There was no statistically significant relationship between knowledge and attitude (r=-.006, p=.944) or knowledge and practice (r=.081, p=.301), but a significant relationship was found between attitude and practice (r=.162, p=.038). Conclusion: UNIMAS undergraduate nursing students possess adequate knowledge and positive attitudes towards blood donation, but their practice habits are poor. Active educational initiatives are needed to improve their knowledge, attitude, and practice regarding blood donation.